Manajemen Logistik Komoditi Telur Ayam dari Peternakan Biosecure - ANAK AGUNG PUTU WULANDARI; I GUSTI AGUNG AYU AMBARAWATI; NI WAYAN SRI ASTITI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2015)
ABSTRACT Logistic Management of Eggs From Biosecure Farm Agribusiness of laying hens is a strategic effort to meet the public demand for eggs. Biosecure farms which implement the program of Clean and Healthy Market Chain (CMC) developed in the ACIAR project, which resulted in good quality chicken eggs, healthy and good for consumption. The farms which obtain a certificate of Indonesian Poultry Biosecurity Center (PBUI) will have the logo of biosecure. The purpose of this study was to determine (1) the logistics management of chicken eggs from the biosecure farms to the consumers (2) the perceptions of stakeholders on the price and quality of eggs from biosecure farms. The method used was descriptive and qualitative analysis to determine the planning, budgeting, procurement, storage, control and distribution. The results showed that (1) logistics management on biosecure farms of chicken eggs commodity can be performed well. It can be seen from the results of weekly livestock production which provides a supply of eggs for PT Mitra Sinar Jaya of 42% and UD Limas Merta Mandiri of 58%. Both agencies will distribute back to the institutional consumer markets (supermarkets and hotels) and a small portion to the traditional markets, (2) the perception of stakeholders on the commodity of chicken eggs from biosecure farms can be categorized as very good with a score of 85.33%. Suggestions which can be given are (1) the logistics management of biosecure farms can expand the distribution channels of healthy chicken eggs for the benefit of consumers, (2) stakeholders of PT MSJ are expected to put biosecure labeling on the packaging, with the aim of attracting consumers in terms of quality. As for UD LMM, it is expected to develop the business of chicken eggs produced by biosecure farms to expand its distribution network. Keywords: Logistics Management, Chicken Eggs, Biosecure, Perception